The Omnibus package in EU food and feed law – balancing the competitiveness of the agri-food sector with consumer protection - Kapała, Anna (Przegląd Prawa Rolnego, 2026)
This article aims to assess whether the legislative proposals included in the Omnibus package maintain a balance between enhancing the competitiveness of the EU agri-food sector and ensuring a high level of consumer protection. The analysis focuses, among other things, on changes to the system for the approval of active substances used in plant protection products, the risk assessment model, and their significance in the context of trade globalization, with particular reference to the phenomenon of so-called ‘boomerang pesticides.’ The proposed measures are intended to simplify and accelerate procedures and to strengthen the competitiveness of the sector. However, they also lead to a reduction in the systematic review of active substances and a gradual shift in the risk assessment model from a precautionary approach towards a more selective one. Moreover, the package does not appear capable of addressing the problem of ‘boomerang pesticides,’ as it maintains a discrepancy between the stringent requirements imposed on EU producers and the rules applicable to the import of food products into the EU market.